PROTECTION OF BANK DEPOSITS IN ISLAMIC JURISPRUDENCE AND ALGERIAN LEGISLATION - Lakhdar, Rabhi; Abdelmadjid, Benyekken (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Bank deposit of all kinds is the main money source and lifeblood of theÂ commercial bank, so that no other party has the right to receive the money from the public. The issue of deposit protection has received considerable attention from Islamic jurisprudence, for its role in achieving economic development through spreading confidence in depositors and increasing deposits, which leads to increased investment and financing operations. The Algerian legislation also gave great attention to bank deposits, with specific and detailed provisions, both in a bank law and in commercial law. Questions have been raised about the concept of bank deposits, its legal nature, and what protection it is for. These are described in this study on the protection of bank deposits in Islamic jurisprudence and Algerian legislation, relying on a collection of references and texts of jurisprudence and legal, as well as some websites. This study covers four axes regarding the relevant concept. First, a conceptual introduction to the key terms in this study. Second, the legal nature of bank deposits. Third, types of bank deposits; fourth, protection of bank deposits.